Agricultural sustainability : progress and prospects in crop research - Bhullar, Gurbir S.; Bhullar, Navreet K. (Academic Press, 2013)
Collaboratively written by top international experts and established scientists in various fields of agricultural research, this book focuses on the state of food production and sustainability; the problems with degradation of valuable sources of land, water, and air and their effects on food crops; the increasing demand of food resources; and the challenges of food security worldwide. The book provides cutting edge scientific tools and methods of research as well as solid background information that is accessible for those who have a strong interest in agricultural research and development and want to learn more on the challenges facing the global agricultural production systems. Provides cutting edge scientific tools and available technologies for research. Addresses the effects of climate change and the population explosion on food supply and offers solutions to combat themWritten by a range of experts covering a broad range of agriculture-related disciplines.